The Autonomisation of the Cultural Field in Late Socialist Albania and the Emergence of Early Sociological Research - Lleshi, Sokol; Starova, Teuta (Stan Rzeczy, 2017)
This paper addresses the following research question: what shaped the emergence of sociological research during the period of late socialism in Albania? The second aim of the paper is to reveal the causal mechanism by which a liberalised cultural policy brought about a shift. The traditional role of the socialist intelligentsia lessened in importance while the role of social scientists emerged. In the very final years of the state socialist regime, in 1989 to 1990, these latter were pitted against Party cadres and representatives in defending a limited yet free academic practice. In order to explain the intricate, early process of the emergence of sociology under state socialism in Albania, this paper utilises a layered theoretical framework that tries to capture the interaction between stages of regime development, the coexistence of various competing modes of legitimation, and the transformation of the heteronomous sector of cultural production into an emergent field of cultural production.